Carbon material dispersion

By using a combination of polymer dispersant with specific structural units, organic solvents and carbon materials, the problem of easy reaggregation of carbon material dispersion at high concentrations is solved, and the coating film formation with excellent stable dispersion and electrical conductivity is achieved. In a variety of products.

CN115916695BActive Publication Date: 2025-02-11DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180048782.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-09
Filing Date
2021-07-02
Publication Date
2025-02-11
Estimated Expiration
2041-07-02

AI Technical Summary

Technical Problem

The existing carbon material dispersion is prone to re-aggregation at high concentrations, and the dispersion performance is insufficient, making it difficult to maintain a stable dispersion state for a long time.

Method used

A polymer dispersant with specific structural units is used to combine organic solvents and carbon materials to stabilize the carbon material through adsorption and dissolution of the polymer dispersant, and a coating film with excellent conductivity is formed.

Benefits of technology

It is realized that carbon materials are difficult to re-aggregate at high concentrations, and are stablely dispersed in the liquid medium to form a coating film with excellent electrical conductivity, which is suitable for various products such as inks and plastic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115916695B_ABST
    Figure CN115916695B_ABST
Patent Text Reader

Abstract

Provided is a carbon material dispersion liquid, which can be used to form various products such as inks that are able to form a coating film having excellent conductivity and in which the carbon material is difficult to reaggregate even at a high concentration and is stably dispersed in a liquid medium containing an organic solvent. The carbon material dispersion liquid contains a carbon material, an organic solvent, and a polymer dispersant, wherein the polymer dispersant is a polymer having 3 to 55% by mass of a structural unit (1) represented by the following general formula (1) (R represents a hydrogen atom, A represents O or NH, B represents an ethylene group, R1 and R2 independently represent a methyl group, Ar represents a phenyl group, X represents a chlorine atom, and p represents an arbitrary number of repeating units), and the polymer dispersant has an amine value of 100 mgKOH / g or less and a number average molecular weight of 5000 to 20000.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a carbon material dispersion. Background Art

[0002] Carbon materials such as carbon black, carbon fiber, carbon nanotube, graphene, graphite (also referred to as "nano carbon materials") have a six-membered ring graphite structure formed by the covalent bonds of carbon atoms. These carbon materials are materials with properties such as electrical conductivity or thermal conductivity, and therefore the use methods utilizing these properties are being studied in many fields. For example, attention is paid to the electrical properties, thermal properties and properties as fillers of carbon materials, and the use methods as antistatic agents, conductive materials and plastic reinforcement materials have been proposed so far. Further, development is being carried out as a material for constituting the cathode lines of semiconductors, fuel cell electrodes, displays, etc.

[0003] These uses are usually used in the form of a carbon material dispersion in which the carbon material is dispersed in a liquid medium such as an organic solvent. In addition, for such a carbon material dispersion, the carbon material is required to be uniformly and stably dispersed in the liquid medium, i.e., excellent dispersibility. Furthermore, it is also required that such dispersibility be maintained stably for a long time. However, nano-sized carbon materials have high surface energy and are easy to aggregate due to the strong van der Waals force. Therefore, there is a problem that even if dispersed, they will immediately aggregate.

[0004] In order to solve this problem, a dispersant is sometimes used to stably disperse the carbon material in a liquid medium. For example, it is proposed to use a cationic surfactant such as an alkanolamine salt or a polymer dispersant such as a styrene-acrylic resin as a dispersant to disperse a carbon material such as a carbon nanotube in a liquid medium (Patent Documents 1 and 2).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2010-174084

[0008] Patent Document 2: Japanese Patent Application No. 2013-537570 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] The carbon material can be dispersed to a certain extent in a liquid medium by using the dispersants proposed in Patent Documents 1 and 2. However, since the dispersibility is insufficient or the material easily reaggregates after dispersion, the dispersibility is not necessarily sufficient, and there is room for further improvement.

[0011] The present invention is completed in view of the problems existing in the prior art, and the technical problem to be solved is to provide a carbon material dispersion liquid that can constitute various products such as inks that can form coatings with excellent conductivity, in which the carbon material is difficult to re-aggregate even at a high concentration and is stably dispersed in a liquid medium containing an organic solvent.

[0012] Solutions for solving problems

[0013] That is, according to the present invention, the following carbon material dispersion can be provided.

[0014] [1] A carbon material dispersion, comprising: at least one carbon material selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite and graphene; an organic solvent; and a polymer dispersant, wherein the polymer dispersant is a polymer having 3 to 55% by mass of a structural unit (1) represented by the following general formula (1), 45 to 90% by mass of a structural unit (3) represented by the following general formula (3), and 0.5 to 20% by mass of other structural units (4) connected to these structural units (wherein the sum of all structural units is 100% by mass), and the polymer dispersant has an amine value of 100 mgKOH / g or less and a number average molecular weight of 5000 to 20000.

[0015]

[0016] (In the general formula (1), R represents a hydrogen atom or a methyl group, A represents O or NH, B represents an ethylene group or a propylene group, R1 and R2 independently represent a methyl group or an ethyl group, Ar represents a phenyl group, a naphthyl group, an anthracene group or a pyrene group, X represents a chlorine atom, a bromine atom, bis(trifluoromethyl)sulfonyl imide or bis(nonafluorobutanesulfonyl)imide, and p represents an arbitrary number of repetitions)

[0017]

[0018] (In the general formula (3), R represents a hydrogen atom or a methyl group, A represents O or NH, Q represents ethylene or methylethylene, Y represents O, NHCOO or NHCONH, m and n independently represent an average number of repeating units of 0 or more, and m+n=20 to 100, R3 represents an alkyl group, an aryl group or an alkylaryl group having 1 to 18 carbon atoms, and r represents an arbitrary number of repeating units)

[0019] [2] The carbon material dispersion according to [1] above, wherein the polymer dispersant is a polymer further comprising a structural unit (2) represented by the following general formula (2).

[0020]

[0021] (In the general formula (2), R represents a hydrogen atom or a methyl group, A represents O or NH, B represents an ethylene group or a propylene group, R1 and R2 independently represent a methyl group or an ethyl group, and q represents an arbitrary number of repetitions)

[0022] [3] A carbon material dispersion according to the above [2], wherein the structural unit (1), the structural unit (2) and the structural unit (3) are respectively represented by the following general formula (1-1), the following general formula (2-1) and the following general formula (3-1), and the structural unit (4) contains a structural unit derived from α-methylstyrene.

[0023]

[0024] (In the general formula (1-1), R1 and R2 independently represent a methyl group or an ethyl group, Ar represents a phenyl group, a naphthyl group, an anthracene group or a pyrene group, X represents a chlorine atom, a bromine atom, bis(trifluoromethyl)sulfonyl imide, bis(nonafluorobutanesulfonyl)imide, and p represents an arbitrary number of repetitions)

[0025]

[0026] (In the general formula (2-1), R1 and R2 are independently methyl or ethyl, and q is an arbitrary number of repetitions)

[0027]

[0028] (In the general formula (3-1), Y represents NHCOO or NHCONH, m and n independently represent the average number of repeating units of 0 or more, and m+n=20 to 100, R3 represents an alkyl group, aryl group or alkylaryl group having 1 to 18 carbon atoms, and r represents an arbitrary number of repetitions)

[0029] [4] The carbon material dispersion according to any one of [1] to [3] above, wherein the content of the carbon material is 15% by mass or less, and the content of the polymer dispersant is 10 to 200 parts by mass relative to 100 parts by mass of the carbon material.

[0030] Effects of the Invention

[0031] According to the present invention, a carbon material dispersion can be provided which can constitute various products such as inks in which a carbon material is stably dispersed in a liquid medium containing an organic solvent and which is unlikely to reaggregate even at a high concentration and can form a coating film having excellent conductivity. DETAILED DESCRIPTION

[0032] <Carbon material dispersion>

[0033] The embodiments of the present invention are described below, but the present invention is not limited to the embodiments described below. The carbon material dispersion of the present invention contains a carbon material, an organic solvent and a polymer dispersant. The polymer dispersant that disperses the carbon material in a liquid medium containing an organic solvent is a polymer having a structural unit (1) represented by the following general formula (1), a structural unit (3) represented by the following general formula (3), and other structural units (4) connected to these structural units. In addition, the amine value of the polymer dispersant is less than 100 mgKOH / g, and the number average molecular weight (Mn) is 5000 to 20000. The specific contents of the carbon material dispersion of the present invention are described below.

[0034] (Carbon material)

[0035] The carbon material is at least one selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite and graphene. As the carbon black, various conventionally known carbon blacks such as acetylene black, furnace black, acetylene black, thermal black and Ketjen black can be used.

[0036] As carbon fibers, PAN-based carbon fibers made of polyacrylonitrile as raw materials, pitch-based carbon fibers made of pitch as raw materials, and their regenerated products can be cited. Among them, so-called carbon nanofibers having a nanometer-sized fiber diameter and a shape in which a six-membered ring graphite structure is wound into a cylindrical shape, and carbon nanotubes having a single nanometer-sized fiber diameter are preferred. Carbon nanofibers and carbon nanotubes can be either multilayer (multi-walled) or single-layer (single-walled).

[0037] The carbon material may also be doped with metals or metal salts such as platinum and palladium. Furthermore, the carbon material may also be surface-modified by oxidation treatment, plasma treatment, radiation treatment, corona treatment, coupling treatment, and the like.

[0038] (Organic Solvent)

[0039] As the organic solvent, any known organic solvent can be used. It should be noted that water can also be used together with the organic solvent. As the organic solvent, hydrocarbon solvents such as hexane, toluene, and xylene; alcohol solvents such as methanol, ethanol, isopropanol, butanol, and dodecanol; ketone solvents such as acetone, methyl ethyl ketone, diethyl ketone, and isobutyl methyl ketone; ester solvents such as ethyl acetate, butyl acetate, amyl acetate, dimethyl succinate, dimethyl adipate, methyl lactate, and dimethyl lactate; ether solvents such as dipropyl ether, tetrahydrofuran, and dioxane; carbonate solvents such as dimethyl carbonate, ethylene carbonate, and propylene carbonate; N,N-dimethylformamide, N,N-dimethylacetamide, pyrrolidone, N-methylpyrrolidone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N, Amide solvents such as N-dimethylpropionamide; urea solvents such as tetramethyl urea and dimethylimidazolidinone; sulfoxide solvents such as dimethyl sulfoxide; glycol monoether solvents such as ethylene glycol, propylene glycol, diethylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, diethylene glycol methyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, and dipropylene glycol monomethyl ether; glycol diether solvents such as ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and dipropylene glycol dimethyl ether; glycol ether monoether ester solvents such as ethylene glycol monomethyl ether acetate, diethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, and propylene glycol monobutyl ether acetate, etc.

[0040] In addition, reactive monomers such as (meth) acrylic monomers, vinyl ether monomers, epoxy compounds, and oxetane compounds can be used as organic solvents. By using such reactive monomers as organic solvents, a carbon material dispersion liquid capable of preparing ultraviolet and electron beam curable inks, ultraviolet and electron beam curable coating agents, etc. can be prepared.

[0041] (Polymer dispersant)

[0042] The polymer dispersant is a polymer having 3 to 55% by mass of a structural unit (1) represented by the general formula (1), 45 to 90% by mass of a structural unit (3) represented by the general formula (3), and 0.5 to 20% by mass of other structural units (4) connected to these structural units (wherein the total of all structural units is 100% by mass).

[0043]

[0044] (In the general formula (1), R represents a hydrogen atom or a methyl group, A represents O or NH, B represents an ethylene group or a propylene group, R1 and R2 independently represent a methyl group or an ethyl group, Ar represents a phenyl group, a naphthyl group, an anthracene group or a pyrene group, X represents a chlorine atom, a bromine atom, bis(trifluoromethyl)sulfonyl imide or bis(nonafluorobutanesulfonyl)imide, and p represents an arbitrary number of repetitions)

[0045]

[0046] (In the general formula (3), R represents a hydrogen atom or a methyl group, A represents O or NH, Q represents ethylene or methylethylene, Y represents O, NHCOO or NHCONH, m and n independently represent an average number of repeating units of 0 or more, and m+n=20 to 100, R3 represents an alkyl group, an aryl group or an alkylaryl group having 1 to 18 carbon atoms, and r represents an arbitrary number of repeating units)

[0047] [Structural unit (1)]

[0048] Structural unit (1) is a structural unit having a quaternary ammonium salt group. As a monomer (monomer 1) that can constitute structural unit (1), for example, a monomer represented by the following general formula (1a) can be cited. It is believed that the adsorption of the quaternary ammonium salt group in the structural unit (1) on the carbon material helps to improve the dispersibility of the carbon material in a liquid medium containing an organic solvent. In addition, one of the substituents bonded to the nitrogen atom of the quaternary ammonium salt group is an aryl methyl group (-CH2-Ar). It is believed that the aromatic ring of the aryl methyl group is affinity with the carbon material, thereby improving the dispersibility of the carbon material. When the number of carbon atoms of R1 and R2 in the general formula (1) is too large, the aryl methyl group becomes unstable due to steric hindrance and it is difficult to form a quaternary ammonium salt group. Therefore, R1 and R2 in the general formula (1) need to be methyl or ethyl independently of each other.

[0049]

[0050] (In the general formula (1a), R represents a hydrogen atom or a methyl group, A represents O or NH, B represents an ethylene group or a propylene group, R1 and R2 independently represent a methyl group or an ethyl group, Ar represents a phenyl group, a naphthyl group, an anthracenyl group or a pyrene group, and X represents a chlorine atom, a bromine atom, bis(trifluoromethyl)sulfonyl imide, or bis(nonafluorobutanesulfonyl)imide)

[0051] Since the quaternary ammonium salt group is an ionic functional group, a polymer (polymer dispersant) having a structural unit (1) containing the quaternary ammonium salt group is expected to exhibit conductivity through water adsorption or ion conduction. That is, by using a polymer having a structural unit (1) as a polymer dispersant, it is expected to produce a carbon material dispersion that can form a coating film with suppressed conductivity reduction.

[0052] The structural unit (1) is preferably represented by the following general formula (1-1).

[0053]

[0054] (In the general formula (1-1), R1 and R2 independently represent a methyl group or an ethyl group, Ar represents a phenyl group, a naphthyl group, an anthracene group or a pyrene group, X represents a chlorine atom, a bromine atom, bis(trifluoromethyl)sulfonyl imide, bis(nonafluorobutanesulfonyl)imide, and p represents an arbitrary number of repetitions)

[0055] The structural unit represented by the general formula (1-1) is composed of, for example, a monomer represented by the following general formula (1a-1).

[0056]

[0057] (In the general formula (1a-1), R1 and R2 are independently methyl or ethyl, Ar is phenyl, naphthyl, anthracenyl or pyrene, and X is a chlorine atom, a bromine atom, bis(trifluoromethyl)sulfonyl imide, or bis(nonafluorobutanesulfonyl)imide)

[0058] Specific examples of the monomer that can constitute the structural unit represented by the general formula (1-1) include dimethylnaphthylmethylammoniumethyl methacrylate chloride, dimethylnaphthylmethylammoniumethyl methacrylate bromide, dimethylnaphthylmethylammoniumethyl methacrylate bis(trifluoromethyl)sulfonyl imide, dimethylnaphthylmethylammoniumethyl methacrylate bis(nonafluorobutanesulfonyl)imide, diethylnaphthylmethylammoniumethyl methacrylate chloride, diethylnaphthylmethylammoniumethyl methacrylate bromide, diethylnaphthylmethylammoniumethyl methacrylate bis(trifluoromethyl)sulfonyl imide, diethylnaphthylmethylammoniumethyl methacrylate Bis(nonafluorobutanesulfonyl)imide, anthracenylmethyldimethylmethylammoniumethyl methacrylate chloride, anthracenylmethyldimethylmethylammoniumethyl methacrylate bromide, anthracenyldimethylmethylammoniumethyl methacrylate bis(trifluoromethyl)sulfonylimide, anthracenyldimethylnaphthylammoniumethyl methacrylate bis(nonafluorobutanesulfonyl)imide, diethylvinylmethylammoniumethyl methacrylate chloride, diethylvinylmethylammoniumethyl methacrylate bromide, diethylvinylmethylammoniumethyl methacrylate bis(trifluoromethyl)sulfonylimide, diethylvinylmethylammoniumethyl methacrylate bis(nonafluorobutanesulfonyl)imide, and the like.

[0059] [Structural unit (2)]

[0060] The polymer dispersant is preferably a polymer further having a structural unit (2) represented by the following general formula (2). By using a polymer further having a structural unit (2) as a polymer dispersant, the dispersibility of the carbon material can be further improved. It should be noted that by quaternizing the amino group in the structural unit (2), a quaternary ammonium salt group in the structural unit (1) can be formed.

[0061]

[0062] (In the general formula (2), R represents a hydrogen atom or a methyl group, A represents O or NH, B represents an ethylene group or a propylene group, R1 and R2 independently represent a methyl group or an ethyl group, and q represents an arbitrary number of repetitions)

[0063] Examples of the monomer (monomer 2) that can constitute the structural unit (2) include monomers represented by the following general formula (2a).

[0064]

[0065] (In the general formula (2a), R represents a hydrogen atom or a methyl group, A represents O or NH, B represents an ethylene group or a propylene group, and R1 and R2 independently represent a methyl group or an ethyl group)

[0066] The structural unit (2) has an amino group as a basic group. Therefore, it is believed that the carboxyl group or phenolic hydroxyl group formed on the surface of the carbon material by oxidation or the like is ion-bonded to the amino group in the structural unit (2), and the polymer dispersant is easily adsorbed on the carbon material, which can further improve the dispersibility of the carbon material. Furthermore, it is believed that the dispersibility of the carbon material can be further improved by the synergistic effect of adsorption on the carbon material with the quaternary ammonium salt group in the structural unit (1) and the polycyclic aromatic group constituting the quaternary ammonium salt group.

[0067] The structural unit (2) is preferably represented by the following general formula (2-1).

[0068]

[0069] (In the general formula (2-1), R1 and R2 are independently methyl or ethyl, and q is an arbitrary number of repetitions)

[0070] The structural unit represented by the general formula (2-1) is composed of, for example, a monomer represented by the following general formula (2a-1).

[0071]

[0072] (In the general formula (2a-1), R1 and R2 are independently methyl or ethyl.)

[0073] Specific examples of the monomer that can constitute the structural unit represented by the general formula (2-1) include dimethylaminoethyl methacrylate and diethylaminoethyl methacrylate.

[0074] [Structural unit (3)]

[0075] Structural unit (3) is a structural unit having a polyalkylene glycol chain. The polymer dispersant having the structural unit (3) is a polymer having a structure in which a polyalkylene glycol chain is grafted. Furthermore, the polyalkylene glycol chain is a molecular chain that can be dissolved in an organic solvent as a dispersion medium. In the general formula (3), the carbamate bond (NHCOO) and urea bond (NHCONH) represented by Y are hydrogen-bonded to hydrogen atoms constituting hydroxyl groups and the like generated on the surface of the carbon material by modification. Therefore, in the polymer dispersant, the polyalkylene glycol chain as a grafted chain is dissolved in the organic solvent as a dispersion medium, and the carbamate bond (NHCOO) or urea bond (NHCONH) in the structural unit (3) and the main chain of the structural unit (1) are adsorbed on the carbon material. Furthermore, the dissolved polyalkylene glycol chain forms a steric hindrance and repels between the granular carbon materials, enabling the carbon material to be well and stably dispersed in the liquid medium for a long time.

[0076] In the general formula (3), m is the average number of repeating units of propyleneoxy (-CH(CH3)CH2O-), and n is the average number of repeating units of ethyleneoxy (-CH2CH2O-). Furthermore, m and n are independently a value greater than 0, and m+n=20 to 100, preferably m+n=35 to 100. That is, the molecular weight of the polyalkylene glycol chain is preferably 880 to 5800, and more preferably 1540 to 5800. It should be noted that in the general formula (3), the alkyl group having 1 to 18 carbon atoms represented by R3 is preferably a methyl group, an ethyl group, a propyl group, a butyl group, a dodecyl group, a stearyl group, a phenyl group, a naphthyl group or a nonylphenyl group.

[0077] Examples of the monomer (monomer 3) that can constitute the structural unit (3) include monomers (macromer) represented by the following general formula (3a).

[0078]

[0079] (In the general formula (3a), R represents a hydrogen atom or a methyl group, A represents O or NH, Q represents ethylene or methylethylene, Y represents O, NHCOO or NHCONH, m and n independently represent an average number of repeating units of 0 or more, and m+n=20 to 100, and R3 represents an alkyl group, an aryl group or an alkylaryl group having 1 to 18 carbon atoms)

[0080] The structural unit (3) is preferably represented by the following general formula (3-1).

[0081]

[0082] (In the general formula (3-1), Y represents NHCOO or NHCONH, m and n independently represent the average number of repeating units of 0 or more, and m+n=20 to 100, R3 represents an alkyl group, aryl group or alkylaryl group having 1 to 18 carbon atoms, and r represents an arbitrary number of repetitions)

[0083] The structural unit represented by the general formula (3-1) is composed of, for example, a monomer represented by the following general formula (3a-1).

[0084]

[0085] (In the general formula (3a-1), Y represents NHCOO or NHCONH, m and n independently represent an average number of repeating units greater than 0, and m+n=20 to 100, and R3 represents an alkyl group, an aryl group, or an alkylaryl group having 1 to 18 carbon atoms)

[0086] Examples of monomers capable of constituting the structural unit represented by the general formula (3-1) include macromonomers in which Y is a urethane bond (NHCOO) obtained by reacting methacryloyloxyethyl isocyanate with a glycol ether monoalkyl ether such as polyethylene glycol monomethyl ether, polyethylene glycol polypropylene glycol monobutyl ether, polypropylene glycol monomethyl ether, and polyethylene glycol monododecyl ether; and macromonomers in which Y is a urea bond (NHCONH) obtained by reacting methacryloyloxyethyl isocyanate with a monoether monoamine such as polyethylene glycol polypropylene glycol monoamine.

[0087] In the general formulas (3), (3a), (3-1) and (3a-1), Y is preferably a urea bond (NHCONH) that does not require a catalyst when reacting isocyanate with amine. In addition, the polyalkylene glycol chain in the general formulas (3), (3a), (3-1) and (3a-1) is preferably a random copolymer of propylene oxide and ethylene oxide. Furthermore, in the general formulas (3), (3a), (3-1) and (3a-1), R3 is preferably a methyl group. It should be noted that the molecular weight of the polyalkylene glycol chain is preferably 2000 to 4000, and preferably m+n=36 to 90.

[0088] [Structural unit (4)]

[0089] Structural unit (4) is another structural unit that can be connected to the above structural unit. Examples of monomers that can constitute structural unit (4) (monomer 4) include (meth)acrylic acid monomers such as (meth)acrylic acid and (meth)acrylates; vinyl monomers such as styrene, vinyltoluene, vinylpyridine, vinylcaprolactone, vinylimidazole, α-methylstyrene, and vinyl acetate. Among them, α-methylstyrene is preferred from the perspective of easy control of molecular weight.

[0090] (Composition and physical properties of polymer dispersants)

[0091] In the polymer dispersant (polymer), the proportion of the structural unit (1) to the total of all structural units is 3 to 55% by mass, preferably 5 to 50% by mass. When the proportion of the structural unit (1) is less than 3% by mass, adsorption on the carbon material becomes insufficient. On the other hand, when the proportion of the structural unit (1) is greater than 55% by mass, solubility in organic solvents becomes insufficient.

[0092] In the polymer, the proportion of structural unit (2) to the total of all structural units is preferably 30% by mass or less, more preferably 2 to 25% by mass. It should be noted that the amine value of the polymer is 100 mgKOH / g or less, preferably 3 to 90 mgKOH / g. When the proportion of structural unit (2) is greater than 30% by mass, the polymer may be colored.

[0093] In the polymer, the proportion of the structural unit (3) to the total of all structural units is 45 to 90% by mass, preferably 50 to 85% by mass. That is, the structural unit (3) is a structural unit contained more in the polymer. By containing more structural units (3), the polyalkylene glycol chains are densely arranged. Therefore, if the polymer as a polymer dispersant is adsorbed on the carbon material, the densely arranged polyalkylene glycol chains become steric hindrances, hindering the approach between the carbon materials, and enabling the carbon materials to be stably dispersed.

[0094] When the proportion of the structural unit (3) in the polymer is less than 45% by mass, sufficient steric hindrance is not formed and it is difficult to improve the dispersibility. On the other hand, when the proportion of the structural unit (3) exceeds 90% by mass, the macromolecular monomer constituting the structural unit (3) may not polymerize and remain because of its slightly poor reactivity.

[0095] In the polymer, the proportion of structural unit (4) to the total of all structural units is 0.5 to 20% by mass, preferably 0.6 to 16% by mass. When the proportion of structural unit (4) is greater than 0.5% by mass, the content of other structural units is relatively reduced, and thus the function as a dispersant is reduced.

[0096] Structural unit (1), structural unit (2) and structural unit (3) are represented by general formula (1-1), general formula (2-1) and general formula (3-1), respectively, and structural unit (4) contains a structural unit derived from α-methylstyrene, which is preferred because it can produce a carbon material dispersion that is more difficult to re-aggregate even when the carbon material is at a high concentration and is more stably dispersed.

[0097] The number average molecular weight (Mw) of the polymer used as the polymer dispersant, measured by gel permeation chromatography (GPC) in terms of polystyrene, is 5000 to 20000, preferably 10000 to 15000. When the number average molecular weight of the polymer is less than 5000, the amount of the structural unit (3) derived from the macromolecular monomer introduced is small, and sufficient dispersion stability cannot be obtained. On the other hand, when the number average molecular weight of the polymer is greater than 20000, the amount of the polymer dispersant required to disperse the carbon material becomes too much, and the viscosity of the obtained carbon material dispersion becomes too high.

[0098] (Synthesis method of polymer dispersant)

[0099] The polymer as a polymer dispersant can be synthesized by an existing known method. For example, it can be synthesized by an existing known radical polymerization method; a polymerization method using a chain transfer agent such as mercaptan to adjust the molecular weight, atom transfer radical polymerization method (ATRP method), reversible addition fragmentation chain transfer polymerization method (RAFT method), nitrogen oxide stable radical polymerization method (NMP method), organic tellurium radical polymerization method (TERP method), iodine transfer polymerization method (ITP method), reversible chain transfer catalytic polymerization method (RTCP method), reversible complex radical polymerization method (RCMP method) and other active radical polymerization methods. Wherein, since the molecular weight of the main chain can be made more uniformly consistent, while forming an AB block copolymer by an addition method, it is preferred to use an active radical polymerization method.

[0100] The polymerization may be any of thermal polymerization and photopolymerization, and an azo-based free radical initiator, a peroxide-based free radical initiator, a photosensitizer, etc. may also be added to the polymerization reaction system. The polymerization form may be any of solvent-free polymerization, solution polymerization, and emulsion polymerization, among which solution polymerization is preferred. By using the same organic solvent as the organic solvent used in the carbon material dispersion during solution polymerization, the polymer after the polymerization reaction can be directly used in the carbon material dispersion, which is preferred.

[0101] For example, by subjecting the above-mentioned monomers to solution polymerization, the target polymer (polymer dispersant) can be obtained. It should be noted that by adding alkyl halides such as benzyl chloride, naphthylmethyl chloride, alkynylmethyl chloride, pyrenemethyl chloride, naphthylmethyl bromide, etc. to the reaction solution obtained by polymerizing the monomers constituting the structural unit (2), the monomers constituting the structural unit (3), and the monomers constituting the structural unit (4), the amino group in the structural unit (2) can be quaternized, and the structural unit (2) can be converted into the structural unit (1). Furthermore, by adding bis(trifluoromethylsulfone)imide lithium salt, bis(heptafluorobutylsulfone)imide lithium salt, etc., the anions (Cl-, Br-) constituting the quaternary ammonium salt can be quaternized. - ) for ion exchange.

[0102] (Carbon material dispersion)

[0103] The content of the carbon material in the carbon material dispersion is preferably set to 15% by mass or less, and more preferably set to 0.5 to 12% by mass. In addition, the content of the polymer dispersant relative to 100 parts by mass of the carbon material is preferably 10 to 200 parts by mass, more preferably 20 to 150 parts by mass, and particularly preferably 30 to 100 parts by mass. When the amount of the polymer dispersant is too little relative to the carbon material, the dispersibility sometimes becomes slightly insufficient. On the other hand, when the amount of the polymer dispersant is too much relative to the carbon material, the ratio of the carbon material is relatively reduced, and the obtained carbon material dispersion becomes easy to increase viscosity.

[0104] The carbon material dispersion may contain resins or additives other than the polymer dispersant. As resins other than the polymer dispersant, for example, polyolefin resins, polyhalogenated olefin resins, polyester resins, polyamide resins, polyimide resins, polyether resins, polyvinyl resins, polystyrene resins, polyvinyl alcohol resins, polymethacrylate resins, polyurethane resins, polyepoxy resins, polyphenol resins, polyurea resins, polyethersulfone resins, etc. As additives, oil-soluble dyes, pigments, ultraviolet absorbers, light stabilizers, antioxidants, leveling agents, defoamers, preservatives, mildew inhibitors, photopolymerization initiators, other pigment dispersants, etc. may be cited.

[0105] (Method for producing carbon material dispersion)

[0106] By using a polymer as a polymer dispersant to disperse the carbon material in a liquid medium containing an organic solvent, a target carbon material dispersion can be obtained. As a method for dispersing the carbon material using a polymer dispersant, an existing known method can be used. Specifically, dispersion methods such as dispersion machine stirring, three-roll mill mixing, ultrasonic dispersion, bead mill dispersion, dispersion using an emulsifier, a high-pressure homogenizer, etc. can be used. Among them, due to the good dispersion effect, it is preferred to disperse by bead mill dispersion, ultrasonic dispersion, and dispersion using a high-pressure homogenizer.

[0107] (Evaluation method of dispersibility of carbon material)

[0108] As a method for evaluating the dispersibility of the carbon material in the carbon material dispersion, there is an absorbance measurement method using a spectrophotometer as shown below. First, a plurality of dispersions containing carbon material at extremely low concentrations and of known concentrations are prepared, and the absorbances of these dispersions at specific wavelengths are measured to prepare a calibration curve that plots the absorbance relative to the concentration of the carbon material. Next, the carbon material, an organic solvent, and a polymer dispersant are mixed and dispersed in an appropriate manner. Thereafter, the incompletely dispersed carbon material is precipitated and separated and removed by centrifugal separation to obtain a supernatant. The obtained supernatant is diluted to a concentration at which the absorbance can be measured, and the absorbance is measured, and the concentration of the carbon material is calculated based on the calibration curve. In addition, the dispersibility of the carbon material can be evaluated by comparing the calculated concentration of the carbon material in the dispersion with the amount of carbon material added.

[0109] Alternatively, the dispersibility of the carbon material may be evaluated by allowing the carbon material dispersion to stand for a long time after centrifugal separation to confirm the presence of aggregates. Furthermore, the carbon material dispersion may be dropped onto a glass plate or the like and the dispersion state may be evaluated using an electron microscope or the like, or the conductivity of a coating formed by applying and drying the carbon material dispersion may be measured and the dispersion state may be evaluated based on whether a predetermined conductivity is reached.

[0110] <Use of Carbon Material Dispersion Liquid>

[0111] The above-mentioned carbon material dispersion can be used as materials such as coatings, inks, plastic products, etc. in which the carbon material is contained in a dispersed state, and it is expected to be used as a conductive material, a thermal conductive material, and an antistatic material. The coating or ink in which the carbon material is contained in a dispersed state can be prepared, for example, by adding a solvent, a resin, and an additive to the carbon material dispersion in a manner to form a prescribed coating composition or ink composition. In addition, the target coating or ink can also be prepared by adding a carbon material dispersion to a commercially available coating or ink. Plastic products in which the carbon material is contained in a dispersed state can be manufactured, for example, by adding a carbon material dispersion to a molten plastic material, mixing, and then removing the solvent. In addition, the desired plastic product can also be manufactured by adding a carbon material dispersion to a plastic material in a fine powder state, mixing, and then removing the solvent, or by precipitating the carbon material.

[0112] Example

[0113] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. It should be noted that, unless otherwise specified, "parts" and "%" in Examples and Comparative Examples are based on mass.

[0114] <Synthesis of polymer dispersants (polymers)>

[0115] (Synthesis Example 1: Polymer Dispersant D-1)

[0116] In a reaction apparatus equipped with a stirrer, a reflux condenser, a thermometer, and a dropping funnel, 100 parts (0.05 mol) of a mono-terminally amino polypropylene glycol polyethylene glycol monomethyl ether (trade name "JEFFAMIN M2005", manufactured by Huntsman Corporation, m+n=35 (m=29, n=6), measured amine value 28.05 mgKOH / g) (M2005) and 100 parts of propylene glycol monomethyl ether acetate (PGMAc) were added, and stirred at room temperature for 10 minutes to make it uniform. In another container, 7.75 parts (0.05 mol) of 2-isocyanatoethyl methacrylate (trade name "Karenz MOI", manufactured by Showa Denko K.K.) (MOI) and 7.75 parts of PGMAC were added and mixed to prepare a mixed solution. The prepared mixed solution was added dropwise to the reaction apparatus over 30 minutes to react. A portion of the reaction solution was sampled for IR measurement, and the disappearance of the isocyanate group derived from MOI and the generation of urea bonds were confirmed. In addition, using a potentiometric automatic titration device, the amine value of the product measured using a 0.1mol / L2-propanol hydrochloric acid solution was 0.1mgKOH / g. Thus, it was confirmed that the reaction of the amino group with the isocyanate group was basically completed. The obtained product is a macromonomer (MCR-1) in which a methacryloyl group is combined at one end of polypropylene glycol polyethylene glycol monomethyl ether (PPG / PEG). The solid content of the MCR-1 solution measured using a moisture meter is 50.0%. In addition, the polystyrene-converted number average molecular weight (Mn) of the MCR-1 measured by gel permeation chromatography (GPC) with tetrahydrofuran (THF) as the developing solution is 3400.

[0117] In a reaction apparatus equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, 49.6 parts of PGMAc, 215.5 parts of MCR-1 solution, 1.8 parts of α-methylstyrene (αMS), 25.1 parts of styrene (St), and 19.2 parts (0.122 mol) of 2-(N,N-dimethylamino)ethyl methacrylate (DMAEMA) were added, and heated while bubbling nitrogen. When the internal temperature reached 70°C, 3.0 parts of dimethyl 2,2'-azobisisobutyrate (trade name "V-601", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (V-601) was added, and the mixture was heated to 75°C for polymerization for 4 hours. 0.5 parts of V-601 was added, and polymerization was further carried out at 75°C for 4 hours. The Mn of the product measured by sampling a portion of the reaction solution was 8500, the dispersion degree (PDI) was 1.65, the peak top molecular weight (PT) was 14000, and almost no peak derived from MCR-1 was observed. The solid content of the reaction solution was 50.1%. In addition, the amine value of the product (converted to resin purity) was 44.6 mgKOH / g.

[0118] At room temperature, a solution of 7.8 parts of PGMAc and 7.8 parts (0.0616 mol) of benzyl chloride (BzCl) was added dropwise over 30 minutes. After the addition, the mixture was heated to 80°C and maintained for 5 hours to obtain a liquid containing polymer dispersant D-1. The Mn, PDI and PT of polymer dispersant D-1 were 8700, 1.66 and 14400, respectively. The solid content of the liquid containing polymer dispersant D-1 was 50.0%. The amine value (calculated as resin purity) of polymer dispersant D-1 was 21.0 mgKOH / g, confirming that the reaction proceeded almost quantitatively. The obtained polymer dispersant D-1 is a resin of amino groups derived from DMAEMA in which 50% of the amino groups are quaternized with BzCl.

[0119] (Synthesis Examples 2 to 5: Polymer Dispersants D-2 to D-5)

[0120] Polymer dispersants D-2 to D-5 were obtained in the same manner as in Synthesis Example 1 except that the formulation shown in Table 1 was used. The abbreviations in Table 1 have the following meanings.

[0121] M41: Monoterminally amino-containing polypropylene glycol polyethylene glycol methyl ether (trade name "Genamin M41 / 2000", manufactured by Clariant Corporation, m+n=41 (m=9, n=32))

[0122] ·DMQ: 2-(N,N-dimethylaminoethyl) methacrylate, benzyl chloride

[0123] MMA: Methyl methacrylate

[0124] The calculation method of the composition of DMQ in Table 1 is explained by taking Synthesis Example 1 as an example. 19.2 parts (0.122 mol) of DMAEMA (Mw 157.1) in the polymer reacts quantitatively with 7.8 parts (0.0616 mol) of added BzCl (Mw 126.6). Therefore, 0.0616 mol × 283.6 = 17.5 parts of DMQ (Mw 283.6) are generated. Below, the composition of DMQ in the polymer is calculated in the same way, taking into account the quaternization rate.

[0125] The calculation method of the theoretical value of the amine value of the polymer is explained by taking Synthesis Example 1 as an example. Half (0.0616 mol) of 19.2 parts (0.122 mol) of DMAEMA in the polymer reacts with BzCl and disappears, so the DMAEMA remaining in the polymer is 0.122×0.5×157.1=9.6 parts. 1g of polymer contains 9.6 / (100+7.75+17.5+9.6+1.8+25.1)×100=0.059g of DMAEMA. Therefore, the amine value can be calculated to be 0.059 / 157.1×56.1×1000=21.1mgKOH / g.

[0126] Table 1: Composition and physical properties of polymers obtained from Synthesis Examples 1 to 5

[0127]

[0128] (Synthesis Example 6: Polymer Dispersant D-6)

[0129] PGMAc 49.5 parts, MCR-1 solution 216 parts, αMS 1.8 parts, benzyl methacrylate (BzMA) 12.5 parts, and DMAEMA 31.7 parts (0.202 mol) were added to a reaction apparatus equipped with a stirrer, a reflux condenser, a thermometer, and a nitrogen inlet tube, and heated while bubbling nitrogen. When the internal temperature reached 70°C, 3.0 parts of V-601 were added, and the polymerization was heated to 75°C for 4 hours. 0.5 parts of V-601 were added and further polymerized at 75°C for 4 hours. The Mn of the product measured by sampling a portion of the reaction solution was 10600, the PDI was 1.89, and the PT was 20200, and almost no peak derived from MCR-1 was observed. The solid content of the reaction solution was 50.1%. In addition, the amine value of the product (converted to resin purity) was 113.2 mgKOH / g.

[0130] The quaternization reaction was carried out in the same manner as in the above-mentioned Synthesis Example 1, except that 17.8 parts (0.101 mol) of 1-chloromethylnaphthalene (CMN) was used instead of BzCl, to obtain a liquid containing polymer dispersant D-6. The Mn of polymer dispersant D-6 was 10900, the PDI was 1.88, and the PT was 20300. The solid content of the liquid containing polymer dispersant D-6 was 50.0%. The amine value of polymer dispersant D-6 (calculated as resin purity) was 32.8 mgKOH / g. The obtained polymer dispersant D-6 is a resin in which 50% of the amino groups derived from DMAEMA are quaternized with CMN.

[0131] (Synthesis Examples 7 and 8: Polymer Dispersants D-7 and D-8)

[0132] Polymer dispersants D-7 and D-8 were obtained in the same manner as in Synthesis Example 6 except that the formulation shown in Table 2 was used. The abbreviations in Table 2 have the following meanings.

[0133] ·CMA: 9-Chloromethylanthracene

[0134] ·CMP: 1-Chloromethylpyrene

[0135] · PME-4000: methacrylic acid-terminated methoxy polyethylene glycol (trade name "BLEMMER PME-4000", manufactured by NOF Corporation, m=0, n=90)

[0136] NQ: 2-(N,N-dimethylaminoethyl) methacrylate, 1-chloromethylnaphthalene salt

[0137] ·AQ: 2-(N,N-dimethylaminoethyl) methacrylate, 9-chloromethylanthracene salt

[0138] ·PQ: 2-(N,N-dimethylaminoethyl)methacrylate, 1-chloromethylpyrene salt

[0139] Table 2: Composition and physical properties of polymers obtained from Synthesis Examples 6 to 8

[0140]

[0141] (Synthesis Example 9: Polymer Dispersant D-9)

[0142] 100.0 parts of a liquid containing polymer dispersant D-2 (50.0% solid content) and 150.0 parts of PGMAc were added to a reaction apparatus equipped with a stirrer, a reflux condenser and a thermometer, and stirred to form a uniform solution. 5.04 parts of lithium bis(trifluoromethanesulfonyl)imide (TFSILi) (0.0176 mol, 30% relative to DMQ) were added and dissolved. Thus, a quaternary ammonium salt with bis(trifluoromethanesulfonyl)imide anion (TFSI) as a counter ion was generated, and a liquid containing polymer dispersant D-9 was obtained. The solid content of the liquid containing polymer dispersant D-9 was 21.5%. The amine value (converted to resin purity) of polymer dispersant D-9 was 21.8 mgKOH / g. When the Mn of polymer dispersant D-6 was to be measured by GPC, it was strongly adsorbed on the chromatographic column and could not be accurately measured. When TFSILi reacts with an equimolar amount of DMQ, an equimolar amount of LiCl (Mw 42.4) is generated. Therefore, the amount of the quaternary salt generated by the reaction of TFSILi and DMQ can be calculated as follows.

[0143] 0.0176mol×(283.7+287.1)-0.0176mol×42.4=9.30 parts

[0144] (Synthesis Examples 10 and 11: Polymer Dispersants D-10 and D-11)

[0145] Polymer dispersants D-10 and D-11 were obtained in the same manner as in Synthesis Example 9 except that the formulation shown in Table 3 was used. The meanings of the abbreviations in Table 3 are as follows.

[0146] DMTFSI: Exchange the chloride ion salt of DMQ into the quaternary salt of bis(trifluoromethanesulfonyl)imide

[0147] DMNFSI: Chloride ion salt of DMQ is exchanged into quaternary salt of bis(nonafluorobutanesulfonyl)imide

[0148] ·NTFSI: Chloride ion salt of NQ exchanged into quaternary salt of bis(trifluoromethanesulfonyl)imide

[0149] Table 3: Composition and physical properties of polymers obtained from Synthesis Examples 9 to 11

[0150]

[0151] (Comparative Synthesis Example 1: Polymer Dispersant HD-1)

[0152] The polymerization was carried out in the same manner as in Synthesis Example 1 except that the formula shown in Table 4 was used and αMS and St were added dropwise using a dropping funnel over 1 hour. The Mn of the product measured by sampling a portion of the reaction solution was 18900, the PDI was 1.85, and the PT was 34300. The solid content of the reaction solution was 50.5%. In addition, the amine value of the product (calculated as resin purity) was 28.5 mgKOH / g.

[0153] A solution of 7.8 parts of PGMAc and 7.8 parts of BzCl (0.0616 mol) was added dropwise at room temperature over 30 minutes. After the addition, the mixture was heated to 80°C and maintained for 5 hours to obtain a liquid containing the polymer dispersant HD-1. The Mn, PDI and PT of the polymer dispersant HD-1 were 19500, 1.84 and 34800, respectively. The solid content of the liquid containing the polymer dispersant HD-1 was 50.4%. The amine value (calculated as resin purity) of the polymer dispersant HD-1 was 13.1 mgKOH / g.

[0154] (Comparison of Synthesis Examples 2 and 3: Polymer Dispersants HD-2 and HD-3)

[0155] Polymer dispersants HD-2 and HD-3 were obtained in the same manner as in Comparative Synthesis Example 1 except that the formulation shown in Table 4 was used. The meanings of the abbreviations in Table 4 are as follows.

[0156] M600: Single-terminally amino-containing polypropylene glycol polyethylene glycol monomethyl ether, trade name "JEFFAMIN M600", manufactured by Huntsman Corporation, m+n=9 (m=9, n=0)

[0157] ·NaBF4: Sodium tetrafluoroborate

[0158] DMBF: DMQ chloride ion salt is exchanged into tetrafluoroborate ion quaternary salt

[0159] Table 4: Composition and physical properties of polymers obtained from Comparative Synthesis Examples 1 to 3

[0160]

[0161] ※: The amount of PGMAc diluted during the salt exchange reaction between NaBF4 and DMQ

[0162] <Manufacturing of Carbon Nanotube Dispersion Liquid>

[0163] (Example 1: CNT dispersion-1)

[0164] 2.0 parts of carbon nanotubes (CNT) (average diameter: 15nm, average length: 3.0μm, MWNT), 94.01 parts of PGMAc, and 3.99 parts of a liquid containing a polymer dispersant D-1 (solid content: 50.1%) were added to a resin container. Although the CNT was wetted by the organic solvent, it sank to the bottom of the container in its original shape, and the supernatant was transparent. A stirrer was added to the container, stirred with a magnetic stirrer, and at the same time, ultrasonic waves were irradiated for 60 minutes using an ultrasonic disperser (power 300W). By irradiating with ultrasonic waves, the liquid uniformly turned black, and the aggregation state of the CNT was released. The solid matter that was not fully dispersed was precipitated and separated and removed by centrifugal separation to obtain CNT dispersion-1.

[0165] (Example 2: CNT dispersion-2)

[0166] Add 2.0 parts of CNT, 94.00 parts of PGMAc, and 4.00 parts of a liquid containing a polymer dispersant D-2 (solid content: 50.0%) to a resin container. Although the CNT is wetted by the organic solvent, it maintains its original shape and sinks to the bottom of the container, and the supernatant is transparent. Use a homogenizer to stir at 8000 rpm for 60 minutes. By stirring with a homogenizer, the liquid turns black uniformly, and the aggregation state of the CNT is released. The solid matter that is not fully dispersed is precipitated and separated and removed by centrifugal separation to obtain CNT dispersion-2.

[0167] (Example 3: CNT dispersion-3)

[0168] 2.0 parts of CNT, 94.02 parts of PGMAc, 3.98 parts of a liquid containing a polymer dispersant D-3 (50.2%), and a diameter of 150 parts of zirconia beads. Although the CNTs were wetted by the organic solvent, they sank to the bottom of the container in their original shape, and the supernatant was transparent. Scandex was used for dispersion treatment for 60 minutes. By using Scandex for dispersion treatment, the liquid became uniformly black, and the aggregation state of the CNTs was released. The solid matter that was not fully dispersed was precipitated and separated and removed by centrifugal separation treatment to obtain CNT dispersion liquid-3.

[0169] (Examples 4 to 11, Comparative Examples 1 to 3: CNT dispersions-4 to 14)

[0170] CNT dispersions 4 to 14 were obtained in the same manner as in Examples 1 to 3 except that the formulation shown in Table 5 was used and the disperser shown in Table 5 was used for the dispersion treatment.

[0171] Table 5: Preparation of CNT dispersion

[0172]

[0173] ※: Amount of liquid containing polymer dispersant

[0174] <Evaluation (1): Evaluation of CNT dispersion>

[0175] Using an E-type viscometer, the viscosity of the CNT dispersion just after dispersion at 25°C was measured. In addition, the CNT dispersion was centrifuged. And, the CNT concentration of the CNT dispersion after centrifugation was measured and calculated using a spectrophotometer. It should be noted that when calculating the CNT concentration, a calibration curve prepared by measuring the absorbance of a sample with a known concentration was used. Furthermore, the dispersion stability (CNT concentration after centrifugation / designed CNT concentration (%)) was calculated. In addition, the CNT dispersion after centrifugation was left to stand for 7 days, and the state of the CNT dispersion after standing was visually confirmed. The results are shown in Table 6.

[0176] Table 6: Evaluation results of CNT dispersion

[0177]

[0178] <Manufacturing of Nanographene Dispersion Liquid>

[0179] (Example 12: NGR dispersion-1)

[0180] 5.0 parts of nanographene (NGR) (average diameter: 5 μm, average thickness: 6-8 nm), 85.02 parts of PGMAc, and 9.98 parts of a liquid containing a polymer dispersant D-1 (solid content: 50.1%) were added to a resin container. A stirring bar was added to the container, stirred by a magnetic stirrer, and ultrasonic waves (power 300 W) were irradiated for 60 minutes using an ultrasonic disperser to obtain NGR dispersion-1 as a viscous liquid.

[0181] (Examples 13 and 14, Comparative Examples 4 and 5: NGR dispersions-2 to 5)

[0182] NGR dispersions-2 to 5 were obtained in the same manner as in Example 12 except that the formulation shown in Table 7 was adopted and the disperser shown in Table 7 was used for the dispersion treatment.

[0183] Table 7: Preparation of NGR dispersion

[0184]

[0185] ※: Amount of liquid containing polymer dispersant

[0186] <Evaluation (2): Evaluation of NGR dispersion>

[0187] The viscosity of the NGR dispersion at 25° C. was measured using an E-type viscometer. In addition, the median diameter (D 50 ). Furthermore, the particle size distribution of the particles in the NGR dispersion was measured using a dynamic light scattering particle size distribution device to confirm the presence or absence of aggregates. The results are shown in Table 8.

[0188] Table 8: Evaluation results of NGR dispersion

[0189]

[0190] <Manufacturing of Carbon Nanofiber Dispersion Liquid>

[0191] (Example 15: CNF dispersion-1)

[0192] Into a resin container, 2.0 parts of carbon nanofiber (CNF) (trade name "VGCF-H", manufactured by Showa Denko K.K., average diameter: 150 nm, average length: 6.0 μm), 94.01 parts of diethylene glycol diethyl ether (DEDG) (trade name "DEDG", manufactured by Nippon Emulsifier Co., Ltd.), 3.99 parts of polymer dispersant D-1 (solid content: 50.1%), and 1.5 parts of ... 150 parts of zirconia beads. Although CNF was wetted by the organic solvent, it sank to the bottom of the container in its original shape, and the supernatant was transparent. The dispersion was treated with an ultrasonic disperser for 60 minutes. The liquid was uniformly blackened by the ultrasonic disperser, and the aggregation state of CNF was released. The solid matter that was not fully dispersed was precipitated and separated by centrifugal separation to obtain CNF dispersion-1.

[0193] (Examples 16 and 17, Comparative Example 6: CNF dispersions-2 to 4)

[0194] CNF dispersions-2 to 4 were obtained in the same manner as in Example 15 except that the formulation shown in Table 9 was used and the disperser shown in Table 9 was used for the dispersion treatment.

[0195] Table 9: Preparation of CNF dispersion

[0196]

[0197] ※: Amount of liquid containing polymer dispersant

[0198] <Evaluation (3): Evaluation of CNF dispersion>

[0199] Using an E-type viscometer, the viscosity of the CNF dispersion just after dispersion was measured at 25°C. In addition, the CNF dispersion was centrifuged. And, the CNF concentration of the CNF dispersion after centrifugation was measured and calculated using a spectrophotometer. It should be noted that when calculating the CNF concentration, a calibration curve prepared by measuring the absorbance of a sample with a known concentration was used. Furthermore, the dispersion stability (CNF concentration after centrifugation / CNF concentration at design (%)) was calculated. In addition, the CNF dispersion after centrifugation was left to stand for 7 days, and the state of the CNF dispersion after standing was visually confirmed. The results are shown in Table 10.

[0200] Table 10: Evaluation results of CNF dispersion

[0201]

[0202] <Manufacturing of Carbon Black Dispersion>

[0203] (Example 18: CB dispersion-1)

[0204] Into a resin container were added 20 parts of carbon black (CB) (trade name "#1000", manufactured by Mitsubishi Chemical Corporation), 68.02 parts of PGMAc, 11.98 parts of a liquid containing a polymer dispersant D-1 (solid content: 50.1%), 1.0 part of a synergist (copper phthalocyanine derivative, trade name "Solsperse 12000", manufactured by Lubrizol Corporation), and a diameter 150 parts of zirconia beads were added and dispersed using an ultrasonic disperser for 30 minutes to obtain CB dispersion-1.

[0205] (Examples 19 and 20, Comparative Example 7: CB dispersions-2 to 4)

[0206] CB dispersions-2 to 4 were obtained in the same manner as in Example 18 except that the formulation shown in Table 11 was used and the disperser shown in Table 11 was used for the dispersion treatment.

[0207] Table 11: Preparation of CB dispersion

[0208]

[0209] ※: Amount of liquid containing polymer dispersant

[0210] <Evaluation (4): Evaluation of CB dispersion>

[0211] The viscosity of the CB dispersion immediately after dispersion was measured at 25° C. using an E-type viscometer. In addition, the median diameter (D 50 ). Furthermore, the viscosity of the CB dispersion liquid at 25° C. after storage at 45° C. for 7 days was measured using an E-type viscometer. The results are shown in Table 12.

[0212] Table 12: Evaluation results of CB dispersion

[0213]

[0214] <Production and evaluation of CNT dispersed ink coating film>

[0215] (Application Example 1)

[0216] To the CNT dispersion-1 obtained in Example 1, an acrylic resin solution (benzyl methacrylate / methacrylic acid copolymer, Mn: 7500, acid value: 100 mgKOH / g, PGMAc solution, solid content: 40%) in an amount of 100 parts of acrylic resin relative to 100 parts of CNT was added. PGMAc was added and diluted in a manner that the CNT concentration was 1% to obtain CNT dispersed ink-1. After applying the obtained ink on the surface of a PET film with a thickness of 100 μm using a rod coater in a manner that the average film thickness becomes 5 μm, it was dried at 130°C for 30 minutes to form a conductive coating. The surface resistance value of the coating was measured using a resistivity meter (trade name "Hiresta", manufactured by NITTOSEIKO ANALYTECH). The results are shown in Table 13.

[0217] (Application Examples 2 to 4, Comparative Application Example 1)

[0218] CNT dispersion inks 2 to 5 were prepared in the same manner as in Application Example 1 except that the CNT dispersion liquids of the types shown in Table 13 were used. Furthermore, conductive coating films were formed in the same manner as in Application Example 1 using the prepared CNT dispersion inks, and the surface resistance values ​​were measured. The results are shown in Table 13.

[0219] Table 13: Characteristics of CNT dispersed ink coating

[0220]

[0221] <Manufacturing of NGR Dispersed Ink Coatings>

[0222] (Application Example 6)

[0223] To the NGR dispersion-1 obtained in Example 12, an acrylic resin solution (benzyl methacrylate / methacrylic acid copolymer, Mn: 7500, acid value: 100 mgKOH / g, PGMAc solution, solid content: 40%) was added in an amount of 100 parts of acrylic resin relative to 100 parts of NGR. PGMAc was added to dilute the NGR concentration to 3% to obtain NGR dispersion ink-1. The obtained ink was applied to the surface of a PET film having a thickness of 100 μm using a rod coater so that the average film thickness became 5 μm, and then dried at 130°C for 30 minutes to form a conductive coating film. The surface resistance value of the coating film was measured using a resistivity meter (trade name "Hiresta", manufactured by NITTOSEIKO ANALYTECH). The results are shown in Table 14.

[0224] (Application Examples 7 and 8, Comparative Application Example 2)

[0225] NGR dispersion inks 2 to 4 were prepared in the same manner as in Application Example 6 except that the NGR dispersion liquids of the types shown in Table 14 were used. Then, conductive coating films were formed in the same manner as in Application Example 6 using the prepared NGR dispersion inks, and the surface resistance values ​​were measured. The results are shown in Table 14.

[0226] Table 14: Characteristics of NGR dispersion ink coatings

[0227]

[0228] <Mixing CNF into resin>

[0229] (Application Example 9)

[0230] Add 3000 parts of solvent (methanol / water = 1 / 1) to a beaker. While stirring with a disperser, slowly add the CNF dispersion-1 obtained in Example 15 to precipitate CNF coated with a polymer dispersant (resin-coated CNF). After filtering the precipitated resin-coated CNF, wash it with methanol and water. Dry it in a dryer to obtain resin-coated CNF (solid content 99.5%).

[0231] Rubber-modified polystyrene resin and 2 parts of resin-coated CNF were mixed with respect to 100 parts of rubber-modified polystyrene resin. Labo Plastomill (manufactured by Toyo Seiki Seisaku-sho) equipped with a T-die was used for extrusion molding to produce a sheet-like evaluation sample with a thickness of about 0.5 mm and a width of 100 mm. The manufactured evaluation sample was punched to produce a sheet with a thickness of about 20 μm. The manufactured sheet was observed using an optical microscope, and no CNF aggregates were observed. Furthermore, the surface resistance value of the manufactured sheet was measured, and the result was 5.26×10 8 Ω / □.

[0232] (Comparative Application Example 3)

[0233] A sheet-shaped sample for evaluation was prepared in the same manner as in Application Example 9, except that CNF dispersion-4 obtained in Comparative Example 6 was used instead of CNF dispersion-1. Furthermore, the prepared sample for evaluation was punched to prepare a sheet having a thickness of about 20 μm. The prepared sheet was observed using an optical microscope, and many CNF aggregates were observed. Furthermore, the surface resistance of the prepared sheet was measured, and the result was 8.38×10 10 Ω / □.

[0234] Industrial Applicability

[0235] The carbon material dispersion of the present invention can be used as a material for manufacturing various products such as battery materials, electronic component trays, IC chip covers, electromagnetic wave shielding devices, automobile components, and robot components, in addition to paints, inks, and plastic products.

Claims

1. A carbon material dispersion comprising: at least one carbon material selected from the group consisting of carbon black, carbon fiber, carbon nanotube, graphite and graphene; an organic solvent; and a polymer dispersant, The polymer dispersant is a polymer having 3 to 55% by mass of a structural unit (1) represented by the following general formula (1), 45 to 90% by mass of a structural unit (3) represented by the following general formula (3), and 0.5 to 20% by mass of other structural units (4) connected to these structural units, wherein: The sum of all structural units is set to 100 mass%, The polymer dispersant has an amine value of 100 mgKOH / g or less and a number average molecular weight of 5000 to 20000. In the general formula (1), R represents a hydrogen atom or a methyl group, A represents O or NH, B represents an ethylene group or a propylene group, R1 and R2 independently represent a methyl group or an ethyl group, Ar represents a phenyl group, a naphthyl group, an anthracene group or a pyrene group, X represents a chlorine atom, a bromine atom, bis(trifluoromethyl)sulfonyl imide, or bis(nonafluorobutanesulfonyl)imide, and p represents an arbitrary number of repetitions; In the general formula (3), R represents a hydrogen atom or a methyl group, A represents O or NH, Q represents ethylene or methylethylene, Y represents O, NHCOO or NHCONH, m and n independently represent the average number of repeating units greater than 0, and m+n=20 to 100, R3 represents an alkyl group, aryl group or alkylaryl group having 1 to 18 carbon atoms, and r represents any number of repetitions.

2. The carbon material dispersion according to claim 1, wherein The polymer dispersant is a polymer further having a structural unit (2) represented by the following general formula (2), In the general formula (2), R represents a hydrogen atom or a methyl group, A represents O or NH, B represents an ethylene group or a propylene group, R1 and R2 independently represent a methyl group or an ethyl group, and q represents an arbitrary number of repetitions.

3. The carbon material dispersion according to claim 2, wherein The structural unit (1), the structural unit (2) and the structural unit (3) are represented by the following general formula (1-1), the following general formula (2-1) and the following general formula (3-1), respectively. The structural unit (4) comprises a structural unit derived from α-methylstyrene, In the general formula (1-1), R1 and R2 independently represent a methyl group or an ethyl group, Ar represents a phenyl group, a naphthyl group, an anthracene group or a pyrene group, X represents a chlorine atom, a bromine atom, bis(trifluoromethyl)sulfonyl imide, bis(nonafluorobutanesulfonyl)imide, and p represents any number of repetitions; In the general formula (2-1), R1 and R2 independently represent a methyl group or an ethyl group, and q represents any number of repetitions; In the general formula (3-1), Y represents NHCOO or NHCONH, m and n independently represent the average number of repeating units greater than 0, and m+n=20 to 100, R3 represents an alkyl group, aryl group or alkylaryl group having 1 to 18 carbon atoms, and r represents any number of repetitions.

4. The carbon material dispersion according to any one of claims 1 to 3, wherein The carbon material content is 15% by mass or less, The content of the polymer dispersant is 10 to 200 parts by mass relative to 100 parts by mass of the carbon material.

Citation Information

Patent Citations

  • Ink containing carbon nanotube

    JP2010174084A

  • Conductive coating composition and method for producing conductive film using the same

    JP2013537570A

  • Polymers

    CN101605829A

  • Agent for dispersing electrically conductive carbon material, and dispersion of electrically conductive carbon material

    CN105473216A